Onomatopoeias and Robert Normandeau’s Sonic World of Baobabs: Transformation, Adaptation, and Evocation - Woloshyn, Alexa (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2014)
For many composers, remaining in the secluded world of the studio allows them to completely internalize their ideas, to control every element, and to realize their exact musical imagination. While Normandeau is certainly most known for his fixed acousmatic works, he does not restrict himself to the closed and controlled world of the electronic music studio. He embraces process, change, and adaptation, in this case adapting the acousmatic work Le renard et la rose (1995) for four singers, six percussionists, and electroacoustics in Baobabs (2012). This article first contextualizes vocal onomatopoeias in 20th-century compositions and Normandeau’s output. Following an overview of the Onomatopoeias cycle and Baobabs, the analysis is divided into rhythm, tonal and formal relationships, and texture and timbre. The article concludes with a reflection on the fundamental differences between the two works, particularly as they relate to control and the composer/performer binary.